Learning Transformation: Increasing Student Achievement through Discovery Learning - Azizah, Imro'atul; Mardiana, Dina (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research aims to improve student learning outcomes by applying strategies of Discovery learning in class IX-E students at SMP Muhammadiyah 8 Batu. Based on Bruner's theory, this research uses a qualitative approach with Classroom Action Research (CAR) types. Data was collected using observation techniques, documentation, and learning results tests from informants of 30 class IX-E students at SMP Muhammadiyah 8 Batu. This CAR was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research results show that the implementation of the Discovery learning strategy in the material on